Biomimetic strategies incorporating enzymes into CaP coatings mimicking the in vivo environment - Martins, Ana M. (2014)
Biomimetic calcium phosphate coating (CaP) methodology mimics the natural biomineralization process of bone, which involves two phases: nucleation and growth. In this chapter we present a successful method to coating biodegradable natural-origin materials with biomimetic CaP layer as a strategy to incorporate enzymes with the main aim of controlling and tailoring their degradation over time. This strategy seems to enhance the bone-bonding, osteoconductive, and osteoinductive properties of natural-origin biomaterials that per se do not present these characteristics.